(1){x+2y=0,3x+4y=6(2){5x+6y=16,7x-9y=5(3){9x-11y+1=0,4x-5y-3=0(4){0.8x-0.9y=2,6x-3y=2.5(5){x=3分之2y+4,y=3分之3x-4(6){x+y=300,5%x+53%y=300×25%
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 09:06:38
(1){x+2y=0,3x+4y=6(2){5x+6y=16,7x-9y=5(3){9x-11y+1=0,4x-5y-3=0(4){0.8x-0.9y=2,6x-3y=2.5(5){x=3分之2y+4
(1){x+2y=0,3x+4y=6(2){5x+6y=16,7x-9y=5(3){9x-11y+1=0,4x-5y-3=0(4){0.8x-0.9y=2,6x-3y=2.5(5){x=3分之2y+4,y=3分之3x-4(6){x+y=300,5%x+53%y=300×25%
(1){x+2y=0,3x+4y=6(2){5x+6y=16,7x-9y=5(3){9x-11y+1=0,4x-5y-3=0
(4){0.8x-0.9y=2,6x-3y=2.5(5){x=3分之2y+4,y=3分之3x-4(6){x+y=300,5%x+53%y=300×25%
(1){x+2y=0,3x+4y=6(2){5x+6y=16,7x-9y=5(3){9x-11y+1=0,4x-5y-3=0(4){0.8x-0.9y=2,6x-3y=2.5(5){x=3分之2y+4,y=3分之3x-4(6){x+y=300,5%x+53%y=300×25%
{3(x+y)-4(x-y)=4 {x+y/2 + x-y/6=1
{x+y=1 ,xy=-6{x(2x-3)=0,y=x²-1{(3x+4y-3)(3x+4y+3)=0,3x+2y=5{(x-y+2)(x+y)=0,x²+y²=8{(x+y)((x+y-1)=0,(x-y)(x-y-1)=0
常微分方程的通解dy/dx=(x-y+1)/(x+y-3)y^4=2y^n+y=0y''+6y'+9y=e^(-3x)y''+y'-2y=4e^(2x)
解二元一次方程组:3(x+y)-4(x-y)=4,x+y/2+x-y/6+1x+y/2+x-y/6+1=1
(x+y)/2- x-y/2=6 3(x+y)=4(x-y)
x+y/3+x-y/2=6 4(x+y)-2(x-y)=40
x+y/2+x-y/3=6,4(x+y)-3(x-y)=-20
{(x+y)/2+(x-y)/3=6 4(x+y)-3(x-y)=-20
4(x+y)-3(x-y)=-20,2/x+y+3/x-y=6
2(x+y)-3(x-y)=1 6(x+y)+(x-y)=51
若2x-3y+4=0则x(x*x-1)+x(5-x*x)-6y+7
{4x-3y-10=0 3x-2y=0,{3x-4(x-y)=2 2x-3y=1,{2(x+y)-(x-y)=3 (x+y)-2(x-y)=1
[(x+2y)²-(x+y)(3x-y)-5y²]÷(2x),其中x,y满足x²+4x+y²-y+17/4=0已知、x+y=6且xy=4(1)x²+y² (2)(x-y)² (3)x{四次方}+y{四次方}第一题没错 书上就这样写的!
解方程组 1.3(x+y)-4(x-y)=4,x+y/2 + x-y/6 =1 2.5x+4y+z=0,3x+y-4z=11,x+y+z=-2
已知X,Y,满足(X+3Y)(X-3Y)=-10(Y^2-6/5)和2X(Y-1)+4(1/2X-1)=0 (X+Y)^2 X^2Y+XY^2注:*/* 是分数
x+y+2(-x-y+1)=3(1-y-x)-4-(y+x-1),x+y=?
x^2+4y^2-6x+4y+10=0,求x^4-y^4/(x+2y)(x-2y)*x+2y/xy^2+y^3除以(x^2+y^2/y)^2的值
(x-y) (x-2y)+(x+2y) (x-3y)-2(x-3y) (x-4y)=